The influence of climatic factors on sunflower ontogenesis in conditions of the Orenburg region - Natalia M. Nazarova; Daria G. Fedorova (RUDN Journal of Agronomy and Animal Industries)
The effect of the variability of certain climatic parameters during the growing season on the cultivation of sunflower (Helianthus annuus L.) in the Orenburg region was studied. It was shown that the growth and development of Helianthus annuus L. are significantly influenced by both humidity and temperature, but the amount of these parameters changes over time due to the ongoing climate change. In this regard, one of the principles of agronomy is to identify relationships between the phases of phenological development in the context of changing weather conditions. It allows to assess the measures aimed at adapting sunflower to a specific cultivation zone. Timely implementation of these measures will enable us to manage the susceptibility of the agricultural sector and predict crop yields. The present study is based on registration of eight phenological phases from sowing to harvesting for three years and assessment of the influence of weather factors of a particular season on both ontogenesis of the crop in general and duration of each phenological phase in particular. According to the results of observations, it was found that the duration of Helianthus annuus L. cv. Poseidon 625 vegetation in climatic conditions of Orenburg region was on average 99 days and is determined by the timing from the formation of the first and second pairs of true leaves to seed formation. The phenological periods requiring maximum moisture were determined from sowing to germination and from flowering to seed filling (r = 0.9, the significance level is 90%). The data obtained during the study can be used by farmers and agronomists to determine the optimal timing of sowing oilseeds not only in Orenburg region, but also in each specific region engaged in their production.